Pengaruh Kombinasi Media Bungkil Kelapa Sawit dan Dedak Padi yang Difermentasi Terhadap Produksi Maggot Black Soldier Fly (Hermetia illucens) Sebagai Sumber Protein Pakan Ikan [The Effect Of Palm Kernel Meal and Rice Bran Media Combination Which Are Fermented To The Production Of Black Soldier Fly Maggot (Hermetia illucens) As A Source Of Fish Feed Protein ] - Muhammad Arief; Azela Noor Ratika; Mirni Lamid (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract The high feed prices caused the cost of feed matters were higher for fish farmers so that needed alternative matter. High prices are caused by fish feed, fish feed ingredients that are imported include fish meal which is the main raw material source of protein to feed the fish so that the necessary alternative feed ingredients for use of fish meal. Maggot can be used as alternative feed matter because it contains crude protein ranged between 30-40% but there are some problems in its production. Media for maggot production used palm kernel meal but the media is hard to find outside of the central plam kernel plantation so as to reduce its use carried out by using a combination of rice bran. Rice bran can be easily to get and can be media for maggot production and low nutrient content of the media production maggot can be corrected through the process of fermentation. This study aims to determine the effect of the combination of media for the production of maggot and find the best combination of media for the production maggot. This research method is to experiment whit Completely Randomized Desing (CRD). The experiment used is 100% palm kernel meal (A), 75% palm kernel meal + 25 rice bran (B), 50% palm kernel meal + 50% rice bran (C), 25% palm kernel meal + 75% rice bran (D) and 100% rice bran with each five replications. The parameters observed were severe maggot production. Analysis of the data used is Analysis of Variance (ANOVA) and to determine the best treatment using Duncan's Multiple range test with a confidence interval of 5%. The results of this study indicate that the combination of palm kernel meal and rice bran are fermented to give a noticeable effect the production Maggot. The best combination of palm kernel meal and rice bran to produce the highest Maggot is the use of palm kernel meal 75% + 25% rice bran are not significantly different with the use of palm kernel meal 100%. Based on this research result shows that the use of 25% of rice bran can reduce the use of 100% palm kernel meal become only 75% in maggot production.